Review of the techniques for estimating population size of Adélie penguins (Pygoscelis adeliae) - Alexandra J. Strang; Elissa Z. Cameron; Dean P. Anderson; Esme Robinson; Michelle A. LaRue (Polar Biology, 2025)
Monitoring of sentinel species provides insight into the ecosystems in which they live. In the Southern Ocean, penguins are one such indicator species, where only a limited number of colonies have been monitored extensively for decades around Antarctica. As the Southern Ocean warms and commercial fishing continues, the need for expansion of population monitoring has become paramount. Using Adélie penguins ( Pygoscelis adeliae ) as a model species, we reviewed methods to estimate colony size including ground and aerial (occupied and unoccupied aircraft) assessment and satellite imagery, with an aim of understanding costs and benefits of each method to inform their future use. Ground assessment includes physically taxing field counts of individuals or nests and was historically the only method used to count penguins in Antarctica. Aerial assessments via occupied and unoccupied aircraft have expanded the spatial extent of monitoring for remote and logistically challenging environments such as Antarctica. Combined with aerial assessment, the more recent use of very high-resolution satellite imagery (VHR) has further expanded Adélie penguin monitoring into previously inaccessible areas. Adélie penguin breeding colonies can be monitored using VHR imagery through the area of their guano stain as a proxy for the number of breeding pairs. Our review provides an overview of the monitoring techniques for Adélie penguins in Antarctica and provides direction for future use and development.